MyHealthAvatar and CARRE: case studies of interactive visualisation for internet‐enabled sensor‐assisted health monitoring and risk analysis. Issue 5 (1st September 2016) - Zhao, Youbing; Parvinzamir, Farzad; Deng, Zhikun; Wei, Hui; Zhao, Xia; Liu, Enjie; Dong, Feng; Clapworthy, Gordon; Lukoševičius, Arūnas; Marozas, Vaidotas; Kaldoudi, Eleni
Abstract : With the progress of wearable sensor technologies, more wearable health sensors have been made available on the market, which enables not only people to monitor their health and lifestyle in a continuous way but also doctors to utilise them to make better diagnoses. Continuous measurement from a variety of wearable sensors implies that a huge amount of data needs to be collected, stored, processed and presented, which cannot be achieved by traditional data processing methods. Visualisation is designed to promote knowledge discovery and utilisation via mature visual paradigms with well‐designed user interactions and has become indispensable in data analysis. In this study the authors introduce the role of visualisation in wearable sensor‐assisted health analysis platforms by case studies of two projects funded by the European Commission: MyHealthAvatar and CARRE. The former focuses on health sensor data collection and lifestyle tracking while the latter aims to provide innovative means for the management of cardiorenal diseases with the assistance of wearable sensors. The roles of visualisation components including timeline, parallel coordinates, map, node‐link diagrams, Sankey diagrams, etc. are introduced and discussed.